The Association Between Metabolic Syndrome and Prostate Cancer Risk: A Large-Scale Investigation and Study of Chinese - Gao, Xiaoshuai; Li, Ruicen; Jin, Tao; Tang, Huairong (Frontiers in Endocrinology, 2022)
Background: To investigate the association between metabolic syndrome (MetS) and its components and prostate cancer (PCa). Methods: This study enrolled 482 943 consecutive men who underwent routine health checkups at the Health Management Center of West China Hospital Between 2010 and 2017. For patients with elevated prostate-specific antigen (PSA) levels or color Doppler ultrasound indicating abnormal prostates, we recommended prostate puncture and follow-up. We used the chi-square test and independent t-test for categorical variables and continuous variables, respectively. We used logistic regression analysis to evaluate the effects of MetS and its components on prostate cancer risk. Results: We found that the incidence of PCa in Chinese men over 40 years of age was 0.1%. Among the 85882 participants, 31.5% (27016/85882) of the patients were diagnosed with MetS. PCa was associated with older age, higher PSA levels, lighter weight and shorter height, hypertension, elevated fasting blood glucose (FBG) and HDL cholesterol level, lower triglycerides. After excluded the interference of other factors in multivariate logistic analysis, we found that MetS, hypertension, hyperlipidemia, hyperglycemia, and obesity were not related to the risk of PCa. High age and PSA levels were risk factors for prostate cancer. Conclusions: High age and PSA levels were risk factors for prostate cancer. MetS, hypertension, hyperlipidemia, hyperglycemia, and obesity were not related to the risk of PCa.